2014
DOI: 10.1038/jes.2014.79
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of childhood lead exposure in the postleaded petrol era: The Tooth Fairy cohort from Newcastle upon Tyne

Abstract: Lead is an environmental contaminant causing irreversible health effects in children. We used dentine lead levels as a measure of early life lead exposure and explored determinants of lead exposure in children living in Newcastle upon Tyne, a historically industrialised UK city, in a cohort born since legislation was introduced to remove lead from petrol, paint and water pipes. The 'Tooth Fairy study' cohort comprised 69 children aged 5-8 years. We collected upper deciduous incisors from children and questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…In this regard, the isotopic composition of blood Pb offers a potential way forward. Blood Pb values can be modelled using existing data for known anthropogenic sources (legacy leaded petrol, PM2.5-10 airborne particulates, coal ash, domestic and imported Pb ores used for the manufacture of in-house Pb pipes) (Hodgson et al, 2015;Shepherd et al, 2009Shepherd et al, , 2016. These will vary according to spatial and demographic factors but will provide an evidence-based isotopic framework for more informed public health intervention measures.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the isotopic composition of blood Pb offers a potential way forward. Blood Pb values can be modelled using existing data for known anthropogenic sources (legacy leaded petrol, PM2.5-10 airborne particulates, coal ash, domestic and imported Pb ores used for the manufacture of in-house Pb pipes) (Hodgson et al, 2015;Shepherd et al, 2009Shepherd et al, , 2016. These will vary according to spatial and demographic factors but will provide an evidence-based isotopic framework for more informed public health intervention measures.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the present study the teeth from both cohorts had been analysed by LA-ICP-MS and provisional data were acquired for the concentration of Pb in enamel and dentine (Shepherd et al, 2012;Hodgson et al, 2015). Comparison with published data indicated that the mean dentine Pb for the Newcastle cohort (0.26±0.16µg/g; n=69) and Billingham cohort (0.18±0.07µg/g; n=15) were significantly lower than the mean value of 2.23±1.32μg/g for deciduous teeth of children living in non-polluted areas of South Africa (Grobler et al, 2000) and the overall means reported for primary school children in Taipei and Boston of 4.4±3.5μg/g and 3.3±2.5μg/g respectively (Rabinowitz et al, 1991).…”
Section: Methodsmentioning
confidence: 99%